Tourism and Growth: Evidence for Spain and Italy - Isabel Cortes-Jimenez; Manuela Pulina (European Regional Science Association (ERSA), 2006)
International tourism is a major foreign exchange earner and a principal export for many low income countries as well as for developed ones. Nowadays many developing countries focus economic policies on promoting international tourism as a potential source of economic growth for the country However, the understanding of the relationship between exports and economic growth is still ongoing and, while cross-section studies support the hypothesis that exports promote growth, time series studies have been less conclusive. This paper has the objective to assess if exports and tourism have really promoted growth at an aggregated level for the two main developed countries in the Mediterranean area, namely Italy and Spain, that represent important countries regarding the expansion of tourism. The methodology applied in this work is a cointegration methodology and the Granger causality test.
Keywords: 330